2022
DOI: 10.1101/2022.08.04.22278407
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predictors of maternal and fetal outcomes of pregnant women with mitral stenosis

Abstract: Background: Valvular heart disease, in particular mitral stenosis, is associated with unfavorable pregnancy outcomes. Data on maternal and fetal outcomes of pregnant women with mitral stenosis in Ethiopia as well as other sub-Saharan countries is scare. Method: A retrospective cross section study was conducted. Chart review of all 58 pregnant women with mitral stenosis admitted at Tikur Anbessa Specialized Tertiary Referral Hospital labor ward from January 2014 to December 2018 was done. Result: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 9 publications
1
3
1
Order By: Relevance
“…In present study, cardiac failure was found to be increased with the severity of mitral stenosis. similar to many studies 7,8,12,16 (table 5). Mitral valve area was the main determinant factor for maternal and fetal outcomes of pregnant women with MS in various studies.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…In present study, cardiac failure was found to be increased with the severity of mitral stenosis. similar to many studies 7,8,12,16 (table 5). Mitral valve area was the main determinant factor for maternal and fetal outcomes of pregnant women with MS in various studies.…”
Section: Discussionsupporting
confidence: 86%
“…Low birth weight babies is due to associated uteroplacental insufficiency leading to low uteroplacental blood flow. In our study the chances of lowbirth weight babies is high in comparison to study by Gebremedhin Y et al 12 , although the still birth rate is similar. This may be as majority of patients arrived late without any prior antenatal check up with small for gestational age babies and mostly had preterm delivery .…”
Section: Discussioncontrasting
confidence: 60%
See 3 more Smart Citations